Synthesis method of high speed finite state machines - Czerwiński, R.; Kania, D. (Bulletin of the Polish Academy of Sciences. Technical sciences, 2010)
The paper is concerned with the problem of state assignment and logic optimization of high speed finite state machines. The method is designed for PAL-based CPLDs implementations. Determining the number of logic levels of the transition function before the state encoding process, and keeping the constraints during the process is the main problem at hand. A number of coding bits, as well as codes for the states, are adjusted to achieve a machine with a determined number of logic levels. Elements of two-level minimization are taken into consideration in the state assignment. The proposed optimization method is based on utilizing tri-state buffers, thus enabling achievement of a one-logic-level output block.